USE OF SORPTION PROCESSES IN THE TECHNOLOGY OF DRUG DELIVERY SYSTEMS - A. V. Bondarev; E. T. Zhilyakova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
The aim of this research is the review of scientific and technical literature regarding possibility of using sorption processes in the technology of drug delivery systems.Materials and methods. The materials are the following electronic resources: eLIBRARY, CyberLeninka, PubMed. The methods of review are analysis and synthesis. The study covers the scientific literature from 1996 up to the present time.Results. Sorbents are used as carriers for various medicinal peroral substances, they are also dispensers of various compounds in the form of polymeric eye films and stents in the human body. The delivery of medicinal substances occurs with the help of sorption processes of mass transfer. Currently, the following medical substances are used as carriers for medicinal substances: activated carbon, mineral sorbents (medical clays, synthetic sorbents), polymers and their biosimilars. 6 groups of pharmaceutical substances are registered for the production of enterosorbents in Russia and they can be used as sorbent carriers in the sorption drug system. They are: activated carbon, colloidal silicon dioxide, polyvinylpyrrolidone, dioctahedral smectite, polymethylsiloxane polyhydrate. As a result of the study, the model of the sorption drug system has been developed. It consists of sorbent carrier, active pharmaceutical ingredient and excipients that provide the desorption. Desorption of the active pharmaceutical ingredient may contribute to its modified release. The technology for obtaining sorption medicinal systems requires further study and development of modeling methods, searching for experimental pharmacological models and technological methods, which make it possible to obtain sorption dosage form with modified release.Conclusion. The review of the sorption processes used in the technology of drug delivery systems has been carried out. The model of the sorption drug system has been developed.